2020
DOI: 10.23736/s1121-421x.20.02656-2
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic colitis: clinical review and 2020 update

Abstract: Anyone can freely access the full text of works made available as "Open Access". Works made available under a Creative Commons license can be used according to the terms and conditions of said license. Use of all other works requires consent of the right holder (author or publisher) if not exempted from copyright protection by the applicable law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 62 publications
(83 reference statements)
0
35
0
3
Order By: Relevance
“…The pathogenesis appears to be a response to ingested and/or inhaled allergens mediated by T-helper 2 cells in the GI tract leading to eosinophilia, chronic inflammation, and GI symptoms [ 9 ]. Eosinophils are normally present within the rest of the GI tract, making the diagnosis of EGID in distal segments of the GI tract more challenging histopathologically, with the lack of clear threshold values for diagnosis [ 10 ]. Management of EGID focuses on symptomatic, endoscopic, and histological improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis appears to be a response to ingested and/or inhaled allergens mediated by T-helper 2 cells in the GI tract leading to eosinophilia, chronic inflammation, and GI symptoms [ 9 ]. Eosinophils are normally present within the rest of the GI tract, making the diagnosis of EGID in distal segments of the GI tract more challenging histopathologically, with the lack of clear threshold values for diagnosis [ 10 ]. Management of EGID focuses on symptomatic, endoscopic, and histological improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike EoE, initial non-pharmacological treatments in EC, including dietary elimination measures, have been of limited effect in the adult population with mixed data [ 10 ]. Oral steroids remain the mainstay of treatment in many cases of EC [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main differential diagnoses to exclude are parasitic infections (Strongyloides stercoralis, Schistosoma spp, Trichuris trichiura, Angiostrongylus costaricencis, Gnathostoma spp, Ascaris lumbricoides, Ancylostoma caninum, Ascaris suum, Enterobius vermicularis and Dientamoeba fragilis and others), some drugs (such as NSAIDs, carbamazepine, rifampin, enalapril, radiotherapy among others), vascular, connective tissue diseases, celiac disease, malignant conditions, and inflammatory bowel disease (IBD). [1][2][3][4] After excluding secondary causes of EC it is important to associate the clinical and epidemiology of the patient such as higher prevalence in females, family history of allergy and age, as the diagnosis is usually made in the adult aged between 33 and 50 years. 2 Laboratory analysis is limited as it has low specificity and sensitivity, but possible to find peripheral eosinophilia which is often transient.…”
Section: Discussionmentioning
confidence: 99%
“…Volume 13 Issue 2 -2022 Isabela Bercovici Soares Pereira, 1 Danilo Queiroz Dantas, 1 Taís Donha Yarid Angelieri, 1 Daniel Yuji Tanaka, 1 Eduardo Achar, 2 Francisco Carillo Neto, 3 João Kleber de Almeida Gentile TCBCD 4 with daily watery diarrhea without mucus or blood for 3 months sought treatment. He reported that the symptoms began after treatment for H. pylori 3 months ago, treated with antibiotics (amoxacillin and clarithromycin).…”
Section: Eosinophilic Ulcerative Colitis -Case Report and Literature ...mentioning
confidence: 99%
See 1 more Smart Citation